2017
DOI: 10.1590/abd1806-4841.20175821
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with exposure to sunlight and sunscreen among physical education teachers in Pelotas, southern Brazil

Abstract: BackgroundDecreasing the time of exposure to the sun and increasing sunscreen use are important actions to prevent skin cancer.ObjectiveThis study aimed to verify the prevalence of exposure to the sun and the use of sunscreen, as well as associated factors among physical education teachers of the basic education network from city of Pelotas, southern Brazil.MethodsA census type study was conducted with physical education teachers of the basic education network from Pelotas. This study assessed the time of expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Among several outdoor occupational groups, 9–86% of the workers applied sunscreen during work (Fig. ) . About one‐third of mountain guides from Germany used sunscreen with a SPF < 30, and only a small share of German outdoor workers checked the SPF of sunscreen before applying it …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several outdoor occupational groups, 9–86% of the workers applied sunscreen during work (Fig. ) . About one‐third of mountain guides from Germany used sunscreen with a SPF < 30, and only a small share of German outdoor workers checked the SPF of sunscreen before applying it …”
Section: Resultsmentioning
confidence: 99%
“…2). 9,16,[36][37][38][39][40][41][42][43][44][45][46][47][63][64][65][66][67][68][69][70][71][72] About one-third of mountain guides from Germany used sunscreen with a SPF < 30, 37,63 and only a small share of German outdoor workers checked the SPF of sunscreen before applying it. 9 Twenty-eight per cent to 86% of different medical professionals applied sunscreen during sun exposure.…”
Section: Sun Protection Behaviourmentioning
confidence: 99%
“…Sunscreen use prevalence in our study is similar to global rates. A study done in Brazil showed that 63% of the population use sunscreen [9]. In a study among primary and secondary school children in Switzerland, 69% of students used sunscreen [10].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, among participants from a Saudi university, the rate of sunscreen use was approximately (35 %) ( NA et al, 2016 ). Comparatively, a study conducted in Brazil reported a higher sunscreen usage rate (63 %) among the population ( Rombaldi et al, 2017 ). Additionally, a study involving primary and secondary school children in Switzerland showed that (69 %) of the participants utilized sunscreen ( Ackermann et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%